SARTRE’S EXISTENTIALISM IN HERMANN HESSE’S DEMIAN: THE STORY OF EMIL SINCLAIR’S YOUTH NOVEL - Mardiani, Lea; Natsir, M.; Nasrullah, Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
This study discussed about the phenomena in the society which human shown their existence and adapted on literary work. This study used Hermann Hesse’s work entitled Demian: The Story of Emil Sinclair’s Youth Novel. This study used Satre’s existentialism study on the ideas of finding the characteristic of Satre’s existentialism in hesse’s works. This study also used Gill and Kenan’s explanation to get through understanding of the main character acts, narrations, dialogs on the research itself. This study aims to examine the characteristic of Sartre’s existentialism in the novel and how the representation of existentialism in the main character. The researcher used qualitative-phenomenology theory to describe human experiences in a certain phenomenon. The results of this research that, there are three conception of Sartre’s existentialism found in main character, Emil Sinclair which is Abandoned by God, Despair and Anguish. Also the researcher concluded that the main character became atheist in the end of the story which he did not choose the two world represent of religion path and the rebellion path. He wants to lives among the society peacefully full of conscious and consideration.